2004
DOI: 10.1523/jneurosci.1339-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Lobe Volume, Function, and β-Amyloid Pathology in a Canine Model of Aging

Abstract: Application of magnetic resonance imaging (MRI) techniques reveals that human brain aging varies across cortical regions. One area particularly sensitive to normal aging is the frontal lobes. In vitro neuropathological studies and behavioral measures in a canine model of aging previously suggested that the frontal lobes of the dog might be sensitive to aging. In the present study, MRI scans were acquired to compare age-related changes in frontal lobe volume with changes in executive functions and ␤-amyloid pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 68 publications
(96 reference statements)
4
117
0
7
Order By: Relevance
“…By the 1950s, researchers observed BAlzheimer's-like^plaque pathology (Dahme 1962(Dahme , 1967(Dahme , 1968Osetowska 1966), which is a result of Ab protein deposition (Cummings et al 1996c). More recent studies have found that dogs have reduced levels of endogenous antioxidants , cortical atrophy (Tapp et al 2004a), ventricular enlargement (Tapp et al 2004a;Su et al 1998), myelin degeneration (Ferrer et al 1993), and accumulation of degraded proteins (Borras et al 1999). However, the canine and human neuropathology is not identical.…”
Section: Brain Aging In the Dogmentioning
confidence: 99%
See 2 more Smart Citations
“…By the 1950s, researchers observed BAlzheimer's-like^plaque pathology (Dahme 1962(Dahme , 1967(Dahme , 1968Osetowska 1966), which is a result of Ab protein deposition (Cummings et al 1996c). More recent studies have found that dogs have reduced levels of endogenous antioxidants , cortical atrophy (Tapp et al 2004a), ventricular enlargement (Tapp et al 2004a;Su et al 1998), myelin degeneration (Ferrer et al 1993), and accumulation of degraded proteins (Borras et al 1999). However, the canine and human neuropathology is not identical.…”
Section: Brain Aging In the Dogmentioning
confidence: 99%
“…Both cognitive dysfunction and cortical atrophy are linked to Ab deposition in the dog (Tapp et al 2004a;Cummings et al 1996b). As mentioned previously, Ab typically is deposited early in the prefrontal cortex of both dogs (Head et al 2000) and humans (Braak and Braak 1997).…”
Section: Brain Aging In the Dogmentioning
confidence: 99%
See 1 more Smart Citation
“…Aged canines show reduced cerebral volume, cortical atrophy and ventricular widening by in vivo magnetic resonance imaging [103,110,111]. The aging canine also shows impairments in visuospatial working memory and executive function [36,102,108].…”
Section: Introductionmentioning
confidence: 99%
“…Cortical atrophy and increased ventricular volume are observed in the aged dog brain (Su et al 1998;Tapp et al 2004;Kimotsuki et al 2005) and may underlie some of the cognitive impairments observed in old dogs. In particular, atrophy in frontal regions may contribute to executive dysfunction .…”
Section: Why Study Aging In Dogs?mentioning
confidence: 99%